Political Economy Effects Of Security Dilemma: Japan’s Involvement In The China-Philippine South China Sea Dispute - Purbantina, Adiasri Putri (Global and Policy Journal of International Relations, 2014)
ABSTRACTThe happening South China Sea dispute between China and its neighbors has taken globalattention. Not just because of regional security matters, the dispute has its potential to drawsUnited States and its alliances to take actions. This study briefly examines the securitydilemma of Philippine in facing China threats in South China Sea. Unfortunately, by draggingJapan inside the dispute, Philippine is facing a serious problem because China has alwaysbeen ready to escalate the dispute. On the other hand, by the opening of Philippine access toJapan, Japan has its benefits to gain political economy advantage from Philippine.Keywords: Regional Security, Security Dilemma, South China Sea DisputeDOI:https://doi.org/10.33005/jgp.v2i02.2063